METHOD OF PREVENTING DORSAL PAIN BY MEANS OF MECHANICAL VIBRATIONS IN THE SPINE’S DEGENERATIVE DISEASES OF DISCAL ORIGIN - Vasile Pâncotan (Romanian Journal of Physical Therapy, 2011)
The purpose of this study is to emphasize the therapeutic value of mechanical vibrations. It is known that the Health Service, after studying their effect on the health of operators, incriminates the effect of vibrations and imposes a series of rules regarding the limitation of their pathogen effect on people’s health and also on the environment. In these cases the mechanical vibrations are considered to be noxae because of long-term exposure. From the studies on people exposed to vibrations also results that these have also benefic effects, depending on the control of their parameters: frequency, amplitude, time and the particular way of applying them on the human body.There are well known vibration-producing appliances on the market which are addressed to the muscle tonifiation or relaxation, in body-building or even in medical treatment as bronchial drainage, osteoporosis etc. The use of mechanical vibrations for the optimization of the intervertebral disc’s functions in the pathology of the degenerative diseases of the spine is a new idea and has become a wide research field on the different mobile areas of the spine. In order to do so we have tested the input of low and medium frequency mechanical vibrations for pain management in dorsal rheumatic affections as compared to the kinetic treatment in order to quantify the separate role of each form of treatment to find out their exact input.